O sucesso de uma Poaceae invasora é associado à resiliência à seca, mas não à competição. - Leal, Rodrigo Pedro (2020)
Biological invasions have been occurring at a faster pace as a result of anthropic actions. At the same time, climate change can increase invasion rates, and also favor invading organisms. One of the predictions for climate change is the increase in periods of drought, in some regions of the planet. In this way, environments that suffer from these disorders become more susceptible to invasion by aquatic plants, especially those that are adapted to different types of habitats. Within this context, the objectives were: (i) to determine the response of a native species (Hymenachne pernambucensis) and another invasive species (Urochloa arrecta) to extreme drought, and (ii) to test whether the interspecific competition between them is affected by stress caused by drought. An in situ experiment was carried out, in which the biomass and the length of the species were different for different levels of drought, in which the invasive species was superior to the native species. However, the intensity of relative competition had only different aerial biomass between species, but in this case the invasive species showed a preference for growth in monoculture than in polyculture. It was concluded, then, that the invasive species U. arrecta has greater resilience to droughts than the native species H. pernambucensis. However, the native species showed greater competitive ability. These results may explain the high dominance of this invasive species in the invaded sites, due to its better resistance to disturbances. In the same way, it demonstrates that native species can reduce the invasion rates of this species, considering that it does not grow well in the presence of neighbors.